An Extensive Survey on Various Set Containment Joins Techniques - Sakthivel, G; Madhubala, P (International Journal of Computer Sciences and Engineering, 2018)
A set containment join is a join between set-valued attributes of two relations, whose join condition is specified using the subset (⊆) operator. Set containment joins are deployed in many database applications, even those that do not support set-valued attributes. In this paper, we study the problem of set containment join. Given two collections R and S of records, the set containment join R ⊆S retrieves all record pairs (r,s) ∈ R × S such that r ⊆ s . This problem has been extensively studied in the literature and has many important applications in commercial and scientific fields. Recent research focuses on the in set containment join algorithms, In this paper, we propose three novel partitioning algorithms, called the Adaptive Pick-and-Sweep Join (APSJ), the Adaptive Divide-and-Conquer Join (ADCJ), and Divide-and-Conquer Join (DCJ) which allow computing set containment joins efficiently. We present a detailed analysis of the algorithms and study their performance on real and synthetic data using an implemented of this algorithm.